THE READING AS AN INVITATION FOR THE TEACHER TO REINVENT THE SCHOOL - Galvao Ribeiro Ferreira, Eliane Ap [UNESP] (Univ Estadual Paulista Julio Mesquita Filho, Fac Ciencias & Tecnologia, 2017)
Free review of the work YUNES, Eliana. Teacher: a learning and its pleasures. Illustration by Bruno Palma e Silva. Curitiba: Hum Publications, 2016. Collection Mediations.
Keywords: Formation of the reader; Reading at school; Reading mediation